Synthesis and aggregation properties of water-soluble newkome-dendronized perylenetetracarboxdiimides - Schmidt, Cordula; Boettcher, Christoph; Hirsch, Andreas (European Journal of Organic Chemistry, 2007)
The synthesis and characterization of three highly water-soluble perylenetetracarboxdiimide ("perylene bisimide", PBI) dyes 1 and 2b is presented. The water solubility is provided by peripheral dendronization with 1G- and 2G-Newkome dendrons. The aggregation behaviour of these amphiphiles in water and that of their tert-butyl-protected precursor molecules 3 and 4 in organic solvents was investigated by UV/Vis- and fluorescence spectroscopy. The symmetric 1G-dendronized dye la forms aggregates more easily than its 2G-counterpart 1b. The asymmetric derivatives 2b reveals pronounced aggregation properties due to the presence of both a 2G-dendron and a flexible and non-bulky dodecyl substituent. The 1G-analogue 2a is insoluble in water as a result of insufficient overall hydrophilicity caused by only one 1G-Newkome dendron. Within the series of water-soluble perylenes 1 and 2b the asymmetric derivative 2b forms the most regularly shaped micelles in water (pH = 7.2) with a mean diameter of 16 nm as demonstrated by transition electron microscopy (TEM). The bola-amphiphiles 1a and 1b form a distribution of smaller aggregates on average with less defined shape. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.